Integrating intraspecific variation in community ecology unifies theories on body size shifts along climatic gradients. (14th November 2016) - Classen, Alice; Steffan‐Dewenter, Ingolf; Kindeketa, William J.; Peters, Marcell K.
Summary: Physiological and energetic mechanisms have been proposed to constrain body sizes of organisms along climatic gradients; however, these provide contrasting predictions. While Bergmann's rule predicts increases in body sizes in cooler climates resulting from physiological constraints, energy‐based community assembly rules suggest declines in the mean body size of species caused by increased extinction probabilities for large‐bodied species in low‐energy habitats. We tested these contrasting hypotheses by quantifying trait distributions in bee communities along a 3·6‐km elevational gradient at Mt. Kilimanjaro. Traditionally, intra‐ and interspecific trait shifts along environmental gradients have been investigated in isolation. However, a surge of theoretical approaches and studies on plants demonstrated that the explicit integration of trait variation among and within species can be essential for identifying the mechanisms that shape traits and related ecosystem functions along environmental gradients. We therefore studied variation in body size and related morphological traits at both the intra‐ and interspecific level. We found support for both physiological constraints and energy‐based community assembly rules as drivers of trait distribution in bee communities along elevational gradients, which, however, affected different levels of biotic organization, that is the population and community level. While the number of bee species with large body sizes declined with elevation, individuals within species became on average larger, resulting in contrasting trends in morphometric parameters at the community versus population level. Furthermore, body size within bee communities became less variable at higher elevations, largely as a result of a non‐random, directive loss of species, but paralleled by a decline in intraspecific variance, suggesting intensified filtering effects with increasing elevation. Similar patterns were found for other functional traits related to the foraging ecology of bees (tongue length, relative forewing length). We conclude that along climatic gradients both physiological and energetic constraints shape trait distributions of pollinators, but at different levels of biological organization. A lay summary is available for this article. Abstract : Lay Summary